2020
DOI: 10.1103/physrevd.101.064008
|View full text |Cite
|
Sign up to set email alerts
|

Extended analysis for the evolution of the cosmological history in Einstein-aether scalar field theory

Abstract: We consider an Einstein-aether scalar field cosmological model where the aether and the scalar field are interacting. The model of our consideration consists the two different interacting models proposed in the literature by Kanno et al. and by Donnelly et al. We perform an extended analysis for the cosmological evolution as it is provided by the field equations by using methods from dynamical systems; specifically, we determine the stationary points and we perform the stability analysis of those exact solutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 78 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…Thus for a healthy theory to be viable, the critical point analysis should provide points where the universe will be accelerating and also these points to be stable. This analysis has been applied in various cosmological models, for instance see and references therein [130,131,[135][136][137][138][139][140][141][142][143][144][145][146][147] .…”
Section: Dynamical Evolutionmentioning
confidence: 99%
“…Thus for a healthy theory to be viable, the critical point analysis should provide points where the universe will be accelerating and also these points to be stable. This analysis has been applied in various cosmological models, for instance see and references therein [130,131,[135][136][137][138][139][140][141][142][143][144][145][146][147] .…”
Section: Dynamical Evolutionmentioning
confidence: 99%
“…Thus for a healthy theory to be viable, the critical point analysis should provide points where the universe will be accelerating and also these points to be stable. This analysis has been applied in various cosmological models, for instance see and references therein [79,80,[84][85][86][87][88][89][90][91][92][93][94][95][96].…”
Section: Dynamical Evolutionmentioning
confidence: 99%

Dynamics in Varying vacuum Finsler-Randers Cosmology

Papagiannopoulos,
Basilakos,
Paliathanasis
et al. 2020
Preprint
“…In addition this analysis provides important information about the initial condition problem. Such analysis has been widely studied in various gravitational models [55][56][57] while some studies in anisotropic universes can be found in [58][59][60][61][62][63][64]. The plan of the paper is as follows.…”
Section: Introductionmentioning
confidence: 99%